Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Motivasi Kerja Pegawai Pada Dinas Tenaga Kerja dan Transmigrasi Kabupaten Pesisir Selatan - Aprimadhani, Lesti; Jhon Rinaldo; Novi Yanti (Fakultas Ekonomi, Universitas Ekasaktii, 2023)
The study aimed to determine the effect of leadership style partially on employee motivation, the influence of organizational culture partially on employee motivation, and the influence of leadership style and organizational culture simultaneously on employee motivation at the Department of Manpower and Transmigration of Pesisir Selatan District. Research methods include field research and library research. The types of data are qualitative data and quantitative data. The data analysis method used is Multiple Linear Regression Analysis, Coefficient of Determination, and Hypothesis Testing using the F test and t-test. The results of the study found that the Leadership Style Variable partially had a positive and significant effect on employee motivation at the Department of Manpower and Transmigration in Pesisir Selatan District. Organizational Culture Variable partially has a positive and insignificant effect on Employee Work Motivation at the Department of Manpower and Transmigration in Pesisir Selatan Regency. Taken together (simultaneously) the variables of Leadership Style and Organizational Culture have an effect on Employee Work Motivation at the Manpower and Transmigration Office of Pesisir Selatan Regency, with an F count of 9.279 with a significant value of 0.001 (p <0.05).